PENGARUH CORPORATE SOCIAL RESPONSIBILITY, PROFITABILITAS, DAN LEVERAGE TERHADAP NILAI PERUSAHAAN - Fenti Arum Farantika; Dwi Ermayanti Susilo (National Conference on Applied Business, Education, & Technology (NCABET), 2021)
This study aims to determine the effect of corporate social responsibility, profitability and leverage on firm value in manufacturing companies listed on the Indonesia Stock Exchange 2017-2020. This study uses quantitative research methods. The population in this study amounted to 181 companies and after going through the purposive sampling method, the number of samples used in this study became 30 companies for 4 years with a total of 120 samples. The type of data used in this research is quantitative by using online document collection techniques in the form of annual reports that have been officially published by the IDX in 2017-2020. Data analysis techniques in this study used descriptive statistical tests, classical assumption tests, Multiple Linear Regression Analysis, t test (partial) and f test (simultaneous). The results showed that Corporate Social Responsibility, Profitability, and Leverage had a significant effect on firm value.